2006
DOI: 10.1038/sj.bjp.0706509
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of experimental colitis in the rat by inhibitors of glycogen synthase kinase‐3β

Abstract: 1 The effects of the inhibitors of glycogen synthase kinase-3b (GSK-3b), TDZD-8 and SB 415286, which can substantially reduce the systemic inflammation associated with endotoxic shock in vivo, have now been investigated on the acute colitis provoked by trinitrobenzene sulphonic acid (TNBS) in the rat. 2 Administration of the GSK-3b inhibitor TDZD-8 (0.1, 0.33 or 1.0 mg kg À1 , s.c., b.i.d., for 3 days) caused a dose-dependent reduction in the colonic inflammation induced by intracolonic TNBS assessed after 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 48 publications
6
69
0
Order By: Relevance
“…As a result, one can hypothesize that, in pathological situations associated with chronic activation of the PAR 2 -GSK3␤ pathway, this might result in impaired mucosal healing, and stem/ progenitor cell resistance to genotoxic insult, mutation accumulation, and acquisition of oncogenic properties. This would be particularly relevant in IBD that have been associated with PAR 2 and GSK3␤ (57,63). The PAR 2 /GSK3␤-induced stem cell survival and proliferation arrest, i.e., quiescence, could also participate in cancer stem cell resistance to therapy (32).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, one can hypothesize that, in pathological situations associated with chronic activation of the PAR 2 -GSK3␤ pathway, this might result in impaired mucosal healing, and stem/ progenitor cell resistance to genotoxic insult, mutation accumulation, and acquisition of oncogenic properties. This would be particularly relevant in IBD that have been associated with PAR 2 and GSK3␤ (57,63). The PAR 2 /GSK3␤-induced stem cell survival and proliferation arrest, i.e., quiescence, could also participate in cancer stem cell resistance to therapy (32).…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] With respect to myocardial IR injury, inhibition of GSK-3β reduces apoptosis and inflammatory indicators (ie, tumor necrosis factor-α and IL-6) in an in vivo model, likely reflecting both systemic and local contributions. 31 Importantly, isolated heart studies, using the Langendorff preparation, have established that the ischemic-reperfused heart mounts a robust inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3␤ inhibitors have been shown to have beneficial effects in animal models of inflammation. Whittle et al (19) have shown that GSK-3␤ inhibitors TDZD-8 and SB 415286 can substantially reduce the systemic inflammation associated with endotoxic shock in vivo and the acute colitis provoked by trinitrobenzene sulfonic acid in the rat. Kinase inhibitors often show nonselective activity, and it is not clear whether the inhibition is entirely because of their effects on GSK-3␤.…”
Section: Discussionmentioning
confidence: 99%